If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2.2) = 6 + -9z Multiply 3 * 2.2 6.6 = 6 + -9z Solving 6.6 = 6 + -9z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '9z' to each side of the equation. 6.6 + 9z = 6 + -9z + 9z Combine like terms: -9z + 9z = 0 6.6 + 9z = 6 + 0 6.6 + 9z = 6 Add '-6.6' to each side of the equation. 6.6 + -6.6 + 9z = 6 + -6.6 Combine like terms: 6.6 + -6.6 = 0.0 0.0 + 9z = 6 + -6.6 9z = 6 + -6.6 Combine like terms: 6 + -6.6 = -0.6 9z = -0.6 Divide each side by '9'. z = -0.06666666667 Simplifying z = -0.06666666667
| 20x+35y=150 | | 7-22-1=9 | | (2x+7)x(x+6)= | | 3(-1)=6-9z | | a^2+n+2b^2= | | x^6+7x-8=0 | | 3a^2(ab^2+b^2)= | | -2x-3x+8=0 | | 3(0)=6-9z | | 0=y+(x/4)-4 | | 3m2=10 | | 7a+12ab-(2a-b)+3b | | 0=n+x-2 | | 4x^3+4x^2=10 | | 3x-8x+7 | | 218=11x+75 | | 3w=6-9(0) | | -46+4x=14 | | 4x-2x=2+6 | | 3w=6-9(-1.4) | | X^2-13=30 | | 5y-15=19 | | 4(2x+2)=1 | | 9x^2-5xy-6y^2 | | (x-6)(4x^2+x-7)=0 | | -8+9+(-7)= | | 5(y-3)=7 | | (9x-1)(7x+4)=0 | | -7+8(-9)= | | 25=1+4x | | -7=-x+1 | | provecos(2x)=2cos^2x-1 |